Developing Inquiry Learning Characteristics of Grade 7 Students Using Integrated 5E’s of Inquiry-Based Learning and Game-Based Learning - Natnaree Thangjai,; Wittaya Worapun, (Journal of Educational Issues, 2024)
Inquiring learning characteristics are desirable learning behaviors that could lead to achievement in science education. The purpose of the study was to investigate the effectiveness of integrated 5E’s of inquiring-based learning and game-based learning management on grade 7 students inquiring learning characteristics. The study was conducted in an action research approach consisting of two learning circles of planning, acting, evaluating, and reflecting. The participants were 8 7-grade students in Anukulnaree School, Thailand using the purposive sampling method. The participants were selected considering their lack of inquiry learning characteristics in class. The instruments were 1) integrated 5E’s of inquiry-based learning and game-based learning management, 2) An inquiring characteristic observation form, 3) an interview form for inquiring characteristics. The data were analyzed by mean score, standard deviation, and effectiveness index with the criterion of 70. The result of the study indicated that at the end of learning circle 2, the effectiveness of integrated 5E’s of inquiring-based learning and game-based learning management on grade 7 students inquiring learning characteristics was at 75/76.36 reaching the criterion set in the study. It could be interpreted that the integration 5E’s of inquiry-based learning and game-based learning as a principle in designing learning management is beneficial in establishing inquiring characteristics in grade 7 students in learning science.